PENGARUH PROFITABILITAS, UMUR PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DAN KOMITE AUDIT PADA KETEPATWAKTUAN PUBLIKASI LAPORAN KEUANGAN TAHUNAN - Pramana, Ari; Ramantha, Wayan (E-Jurnal Akuntansi, 2015)
Timeliness of the publication of the financial statements is a very important for the company. Because the information contained in the financial statements is very helpful for investors and decision makers. There are several factors that affect the timeliness of the publication of the annual financial statements include profitability, firm age, institutional ownership, independent commissioners and audit committee. The population in this study are all banking companies listed in Indonesia Stock Exchange during 2011-2013. The number of samples used in this study is the 78th of data analysis techniques used to solve these problems is the multiple regression analysis. Based on the results of analysis known that profitability, firm age, and independent commissioners positive effect on the timeliness of the publication of the annual financial statements of the banking company in Indonesia Stock Exchange 2011-2013. While institutional ownership and audit committee does not affect the timeliness of the publication of the financial statements of the banking company in Indonesia Stock Exchange 2011-2013.
Keywords: timeliness, profitability, firm age, institusional ownership, independent directors, and audit committee